THE INFLUENCE OF WORK MOTIVATION, TRAINING AND WORK PERFORMANCE DISCIPLINE OF THE STATE CIVIL APPARATUS AT CIVIL SERVICE POLICE UNIT KNOWN AS “SATPOL PP” AND MERAUKE DISTRICT FIRE DEPARTMENT - Irianto Sabar Gattang; Ferdinandus Christian; Anshar Daud (STED Journal, 2022)
This study aims to examine and analyze the influence of work motivation, training and work discipline of the State Civil Apparatus at Civil Service Police Unit known as “Satpol PP” and Merauke District Fire Department. This study used an associative quantitative approach using saturated sample techniques so that the number of samples amounted to 106 people. Data sources use primary data and secondary data with data collection techniques through field studies and literature studies. Measurement of variables is done using the Likert scale with data analysis done by using Statistic Product and Service Solutions (SPSS). The results of the analysis shows that the motivation of the work had no influence on the performance of the State Civil Apparatus at Civil Service Police Unit and Merauke District Fire Department. Those Training effects on the work performance of the State Civil Apparatus at Civil Service Police Unit Office and Merauke District Fire Department. The Work discipline affects the performance of the State Civil Apparatus at Civil Service Police Unit and Merauke District Fire Department. The results of the determination test shows that the variables of work motivation, training and work discipline had an effect on the performance of the State Civil Apparatus at the Civil Service Police Unit and Merauke District Fire Department by 67.8% and the remaining by 32.2% were other variables that were not examined in this study.